Diseño de un sistema de gestión y de control operacional en una estación de servicio. - Allauca Fernandez, Johanna E. (2009)
This paper presents the design of an asset management system through the TPM, 5 S'sy other methodologies, in a service station, located in the city of Playas for 2008. We developed the documentation of the pillars of TPM for use in decision making. Key concepts have been used for Asset Management, also all the terms and definitions used in the development of this research work. In addition to analysis of the methodologies applied. In addition there is to know the history of the company and its origins, mission, vision, organizational structure and description of main activities according to the pillars of TPM. It covers the design of each pillar for the implementation of TPM in the company, also analyze the most important variables for making decisions, we use statistical techniques to improve the interpretation of the values of each indicator. The 5 S's program for the service station as an opportunity for improvement and we will obtain the economic analysis with the TPM. At the end draws the conclusions and recommendations at each stage of the asset management system.